2020
DOI: 10.1007/s00122-020-03579-z
|View full text |Cite
|
Sign up to set email alerts
|

Fine mapping qGL2H, a major locus controlling grain length in barley (Hordeum vulgare L.)

Abstract: Key message A major grain length QTL on chromosome 2H was fine mapped to a 140.9 Kb region containing three genes. Abstract Increasing yield is an important target for barley breeding programs. One approach to increase yield is by enhancing individual grain weights through the regulation of grain size. Fine mapping major grain size-related quantitative trait loci is necessary for future marker-assisted selection strategies, yet studies of this nature are limited in barley. In the present study, we utilised a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 52 publications
1
19
1
Order By: Relevance
“…Among the four identified significant QTL for GL, QGl.NaTX-2H and QGl.NaTx-3H were less affected by environments and determined a large percentage (29.8% and 21.9%, respectively) of phenotypic variation ( Table 3 ). A major QTL for GL have been reported on 2H from the cross of Vlaminh and Buloke which is located at 70-80 cM in one report ( Walker et al, 2013 ) but at 159–179 cM in another report ( Watt et al, 2019 ) which is further fine mapped to a 140.9 Kb interval ( Watt et al, 2020 ). The QTL are apparently different from our major QTL on 2H for GL which was located at 10.02 cM ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the four identified significant QTL for GL, QGl.NaTX-2H and QGl.NaTx-3H were less affected by environments and determined a large percentage (29.8% and 21.9%, respectively) of phenotypic variation ( Table 3 ). A major QTL for GL have been reported on 2H from the cross of Vlaminh and Buloke which is located at 70-80 cM in one report ( Walker et al, 2013 ) but at 159–179 cM in another report ( Watt et al, 2019 ) which is further fine mapped to a 140.9 Kb interval ( Watt et al, 2020 ). The QTL are apparently different from our major QTL on 2H for GL which was located at 10.02 cM ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…ABC transporters play critical roles in plant growth and development, especially for the development of specialized plant cells ( Do, Martinoia & Lee, 2018 ) and regulation of root cell growth ( Larsen et al, 2007 ). MYB transcription factor is also proposed to be the candidate for GL ( Watt et al, 2020 ). It is linked with cell growth and seed production through interacting with plant hormones, playing roles in sperm-cell, stamen development, cotton fibre and even stomatal cell divisions ( Lai et al, 2005 ; Rotman et al, 2005 ; Pu et al, 2008 ; Zhang et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The subsequent sequencing results showed that the same single base insertion was found in the CDS of parent GP, which revealed the identity of qGL5/qTGW5 and HvDEP1. In addition, through different populations, several major QTLs for GL have been mapped on chromosome 2, 3, 4, 5, 6, and 7H, and no major QTL was found on chromosome 1H (Walker et al, 2013;Zhou et al, 2016;Watt et al, 2019Watt et al, , 2020. So, qGL1 should be an unreported new QTL for GL.…”
Section: Discussionmentioning
confidence: 99%
“…The consistent relationship between the promotor polymorphism and grain length across environments, showing a stable influence of promoter polymorphism, indicates that grain length is much less influenced by environment than is TGW. This is unsurprising given grain length has high heritability compared with TGW, which is controlled by several interrelated factors not exclusive of grain size (Avni et al 2018;Roy and Shil 2020;Watt et al 2020). However, the positive correlations between grain length and TGW suggest that this polymorphism would still be useful for MAS improvement of TGW, and hence grain yield, which typically has much lower heritability.…”
Section: Discussionmentioning
confidence: 99%